Emancipação, políticas públicas e educação ambiental: caminho para a formação cidadã a partir do projeto político pedagógico para o Rio Araguari (MG) - Naves, João Gabriel de Paula (2022)
Developed in the context of the Public Policy on Water Resources, Environmental Education is, like any pedagogical act, always a rich opportunity for the social and individual development of societies and populations in constant transformation. In the current conjuncture of the world, mapped in this thesis from the concepts of the Sociocultural Project of Modernity by Boaventura de Souza Santos and the Modern-Colonial World-System by Emmanuel Wallerstein, by Carlos Walter Porto-Gonçalves and by Rogério Haesbaert, Education configures, however, more a mechanism for regulating social conditions than an instrument of human emancipation. Therefore, less changeable than what was necessary and imagined by Paulo Freire, another vector for the formation of this research. In this sense, I seek to highlight with this thesis the possibility of making Environmental Education, developed from the Hydrographic Basin Committees and from the National Water Resources Policy, a reference to the socio-environmental training of subjects, as long as it is planned from a perspective that be liberating, emancipatory, democratic, sustainable and citizen. This proposal is based on the principles of Political Ecology and Environmental Rationality, present in Enrique Leff's thinking, in Participatory Democracy, in Jünger Habermas' Theory of Communicative Action, in the latent decolonial wills of the peoples of Latin America and, above all, in the very attributions regimented by law for the development of the educational process of Environmental Education in non-formal environments; that is, the works based on public governmental policies. This whole construct gives rise to a certain hope of instilling Environmental Education for Environmental Management, by José da Silva Quintas and Maria José Gualda, in the guidelines of application and development of the educational process offered based on the PNRH. The idea of this thesis is to work on Education for Environmental Management from Pedagogical Political Projects, aimed at the practice of Environmental Education developed within the scope of the Brazilian Hydrographic Basin Committees. The objective is the collective construction of the individual, social and territorial identity of the various relationships of society-nature, made possible, in these cases, from the care with the waters, with nature (including human) and with the territories of the hydrographic basins. Finally, in order to suggest something that also goes beyond the important academic discussions, I propose a reflection on Environmental Education developed by CBH-Araguari (MG). This happens through the suggestion of the “Political Pedagogical Project for CBH-Araguari (MG)”, a document that condenses the entire discussion of this thesis into a political-pedagogical arrangement that guides the practice of Environmental Education offered by this committee, whose space for discussion and deliberation is important for every society.